2020
DOI: 10.3390/nu12113324
|View full text |Cite
|
Sign up to set email alerts
|

Is the Perceived Fruit Accessibility Related to Fruit Intakes and Prevalence of Overweight in Disadvantaged Youth: A Cross-Sectional Study

Abstract: Background: Few investigations have studied the relationship between home and school food environments, fruit intakes, and prevalence of overweight in children and adolescents from disadvantaged backgrounds. This study aimed to determine whether food environments for fruit intake at household and school levels affect fruit intakes and risk of overweight among children and adolescents with low household income. Methods: Students (n = 3148) in Seoul, Korea completed questionnaires pertaining to select aspects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…However, our study shows that compared with participants meeting the fruit intake guidelines, those who did not meet the fruit intake guidelines showed significantly lower risks of overweight/obesity. Most previous studies did not distinguish the ways of consuming fruits, such as fresh whole fruits, 100% fruit juice, blended juice or tinned fruit, leading to inconsistent results on the association between fruit consumption and weight [ 70 , 71 , 72 , 73 ]. Fruit contains various kinds of simple sugars (glucose, fructose, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our study shows that compared with participants meeting the fruit intake guidelines, those who did not meet the fruit intake guidelines showed significantly lower risks of overweight/obesity. Most previous studies did not distinguish the ways of consuming fruits, such as fresh whole fruits, 100% fruit juice, blended juice or tinned fruit, leading to inconsistent results on the association between fruit consumption and weight [ 70 , 71 , 72 , 73 ]. Fruit contains various kinds of simple sugars (glucose, fructose, etc.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support our results. Additionally, previous studies found that low socioeconomic status and fruit intakes were associated with adolescent overweight/obesity [ 73 , 78 ]. Fruit intakes mediated the relationship between low socioeconomic status and adolescent overweight/obesity [ 78 ].…”
Section: Discussionmentioning
confidence: 99%